Hubungan Layanan Konseling Individu Dengan Kepercayaan Diri Siswa Kelas VII SMP Negeri 6 Kota Serang Tahun Ajaran 2019/2020 - Amelia Putri, Juana; Nurmala, Meilla Dwi; Afiati, Evi (Jurnal Pendidikan Indonesia, 2022)
Abstracts written in Indonesian with a maximum of 250 words. Times This diary is intended to determine the relationship between individual counseling services and the confidence of Grade VII students of SMP Negeri 6 Kota Serang. This research is in the form of quantitative research, namely data collection using library research, observations, interviews, documents and questionnaires. Then analyzed by statistical analysis, namely linearity and hypothesis testing. The results obtained from the study were that low grade students accounted for 30.55%, average graded students accounted for 77 students with the rate of 53.47 n high grade students had 23 students with a rate of 15.97%. Overall, Personal Counseling Services students have moderate criteria with a rate of 53.47%. The conclusion of the study is that the relationship between counseling services and student confidence is correlated with a correlation value of 0.713 and a percentage of 71.3%. Recommendations For instructors and counselors in schools, it is hoped that they can provide group and individual counseling for the purpose of correcting students' confidence issues